Early clear cell "sugar" lung cancer management: A case report and a brief literature review. Issue 5 (16th April 2019) - Sjniari, Marsela; Miele, Evelina; Stati, Valeria; Di Cristofano, Claudio; Diso, Daniele; Pecoraro, Ylenia; Venuta, Federico; Tomao, Silverio; Spinelli, Gian Paolo
Abstract : A clear cell tumor is a histological entity that rarely originates outside of the kidney. We describe a rare case of a clear cell tumor of the lung, also known as "sugar cancer, " that occurred in a 74 year‐old male patient, and perform a brief literature review. This report highlights the importance of an adequate disease management team, including surgeons, oncologists, and pathologists, to identify the best therapeutic approach to improve survival rates and the quality of life of patients affected by this rare disease.